Inhibition of 11beta-hydroxysteroid dehydrogenase in guinea pig kidney by three bioflavonoids and their interactions with gossypol. - WANG Mao-Shan; SHI Hong; WANG Ke-Shen; REIDENBERG Marcus M (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of some bioflavonoids on the gossypol-induced hypokalemia. METHODS: The 11beta-hydroxysteroid dehydrogenase (11beta-OHSD) protein was prepared from guinea pig kidney. The activity of 11beta-OHSD with NAD as the coenzyme was measured by HPLC. The drug interaction was analysed by isobolographic method. RESULTS: The 11beta-OHSD can be inhibited by some bioflavonoids. The IC50 (95 % confidence limits) values were: quercetin 164 (79 - 341) micromol/L, morin 913 (385 - 2173) micromol/L, and naringenin 2193 (1114 - 4315) micromol/L. When the 11beta-OHSD was treated with quercetin, tangeretin, morin, naringenin plus gossypol, the combination index (CI) values were 0.92, 0.85, 0.98, and 1.01 respectively. CONCLUSION: The interaction of some bioflavonoids with gossypol might be one of the factors for gossypol-induced hypokalemia.